PERAN ASATIDZ DALAM PEMBENTUKAN KARAKTER SANTRI BARU DI PONDOK MODERN DARUSSALAM GONTOR KAMPUS 7 KALIANDA LAMPUNG SELATAN - Jasendra Adiyatma; Arizal Eka Putra; Tahir Rohili (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Character formation of santri is a fundamental objective of education in Islamic boarding schools, particularly for new students who are in the process of adapting to the values and culture of the pesantren. The role of asatidz is crucial in guiding santri and instilling moral and spiritual values that shape their character. This study aims to analyze the role of asatidz in the character formation of new santri at Pondok Modern Darussalam Gontor Campus 7 Kalianda. This research employed a qualitative method with a field research approach. Data were collected through in-depth interviews, observations, and documentation. The findings indicate that asatidz play a strategic role in shaping santri’s character through the internalization of the values of the Panca Jiwa, namely sincerity, simplicity, self-reliance, Islamic brotherhood (ukhuwah Islamiyyah), and freedom. Character formation is implemented through four main methods: role modeling, habituation, moral advice, and the application of educational punishment. Role modeling is identified as the most effective method as it provides direct examples for santri. Habituation is carried out through daily routines to foster consistent character development, while advice and punishment function as tools for moral reinforcement, discipline, and responsibility. This study emphasizes that character education in pesantren extends beyond academic aspects to include the development of faith, worship, and morality, contributing to the formation of santri who are morally upright, independent, and responsible.